The Impact of Climate Change on Global Tropical Storm Damages - Mendelsohn, Robert; Emanuel, Kerry; Chonabayashi, Shun (2012)
This paper constructs an integrated assessment model of tropical cyclones in order to quantify the impact that climate change may have on tropical cyclone damages in countries around the world. The paper relies on a tropical cyclone generator in each ocean and several climate models to predict tropical cyclones with and without climate change. A damage model is constructed to compute the resulting damage when a cyclone strikes each country. Economic development is expected to double global tropical cyclone damages because more will be in harm's way. Climate change is expected to double global damage again, causing an additional $54 billion of damage per year. The damage is projected to be concentrated in North America and eastern Asia but many Caribbean islands will suffer the highest damages per unit of GDP. Most of the increased damage will be caused by rare but very powerful storms.